Thrombospondin 1 (THBS1) Promotes Follicular Angiogenesis, Luteinization, and Ovulation in Primates - Bender, Hannah R.; Campbell, Genevieve E.; Aytoda, Priyanka; Mathiesen, Allison H.; Duffy, Diane M. (Frontiers in Endocrinology, 2019)
Angiogenesis is essential to both ovulation and the formation of the corpus luteum. The thrombospondin (THBS) family of glycoproteins plays diverse roles in regulation of angiogenesis, but the role of these vascular regulators in ovulation and luteinization remain to be elucidated. Using the cynomolgus macaque as a model for human ovulation, we demonstrated that levels of THBS1 mRNA and protein in preovulatory follicle granulosa cells increased after the ovulatory gonadotropin surge, with peak levels just before the expected time of ovulation. THBS1 treatment of monkey ovarian microvascular endothelial cells in vitro stimulated migration, proliferation, and capillary sprout formation, consistent with a pro-angiogenic action of THBS1. Injection of an anti-THBS1 antibody into monkey preovulatory follicles reduced rates of follicle rupture and oocyte release in response to an ovulatory gonadotropin stimulus when compared with control IgG-injected follicles. Interestingly, two of three oocytes from anti-THBS1 antibody injected follicles were germinal vesicle intact, indicating that meiosis failed to resume as anticipated. Follicles injected with anti-THBS1 antibody also showed reduced granulosa cell layer expansion, endothelial cell invasion, and capillary formation when compared to control IgG-injected follicles. Overall, these findings support a critical role for THBS1 in follicular angiogenesis, with implications for both successful ovulation and corpus luteum formation.